Innovation and Export Competitiveness: Evidence from Georgia Firms (European Journal of Marketing and Economics, 2023)
Innovation has long been recognized as a cornerstone for establishing and sustaining the competitiveness of both nations and individual firms within the global marketplace. This study investigates the specific relationship between innovation and export intensity by utilizing data from the World Bank Group’s Enterprise Surveys, focusing specifically on Georgian enterprises. Through an empirical analysis of 360 firms, the research highlights how various innovative activities influence international trade performance. The findings reveal that the introduction of innovations—particularly product innovations—serves as a primary driver of export intensity. Georgian firms that are deeply integrated into the innovation process consistently report the highest levels of export activity. Furthermore, the magnitude of this impact is substantial, suggesting that strategic investments in research and development are not merely beneficial but essential for scaling operations abroad. Ultimately, the study underscores that for Georgian firms to thrive globally, fostering a robust internal culture of innovation is a critical prerequisite for success.
Keywords: Innovation; Technological progress, Export competetvness, Productivity